DISASTERS AND ENVIRONMENTAL MANAGEMENT IN THE DONGTING LAKE LOWLANDS - R.– L. Yin; D.- X. Shen; Z.- G. Che (International Association of Lowland Technology, 2003)
Dongting Lake is one of the most important freshwater lakes in China. There is a dense population and richresources in the lake region that is also an important natural ecological system. The Dongting Lake lowlands have always been a serious flood disaster region, and human activities have impacted negatively on the ecological environment. In response, the Chinese government has adopted a series of structural and non-structural measures, resulting in mitigation of flooding disasters and improving the environmental protection in the lake region.